2002
DOI: 10.1164/rccm.2111021
|View full text |Cite
|
Sign up to set email alerts
|

Association between Air Pollution and Lung Function Growth in Southern California Children

Abstract: A cohort of 1,678 Southern California children, enrolled as fourth graders in 1996, was followed for 4 years to determine whether the growth in lung function of the children was associated with their exposure to ambient air pollutants. These subjects comprised the second cohort of fourth grade children participating in the Children's Health Study. Significant deficits in lung function growth rate were associated with exposure to acid vapor, NO(2), particles with aerodynamic diameter less than 2.5 microm (PM(2.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
285
1
5

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 407 publications
(301 citation statements)
references
References 32 publications
(12 reference statements)
10
285
1
5
Order By: Relevance
“…Contrary to initial expectations, the research indicated no significant differences in the average values of the PF tests across the townships, despite their distinctively different air pollution levels and the wealth of evidence accumulated to date on the link between air pollution and PF development in children (see inter alia Peters et al, 1999a, b;Pikhart et al, 2000;Gauderman et al, 2000Gauderman et al, , 2004Schwartz, 2004).…”
Section: Hadera Region Israel As a Case Studycontrasting
confidence: 64%
“…Contrary to initial expectations, the research indicated no significant differences in the average values of the PF tests across the townships, despite their distinctively different air pollution levels and the wealth of evidence accumulated to date on the link between air pollution and PF development in children (see inter alia Peters et al, 1999a, b;Pikhart et al, 2000;Gauderman et al, 2000Gauderman et al, , 2004Schwartz, 2004).…”
Section: Hadera Region Israel As a Case Studycontrasting
confidence: 64%
“…Major sources of nitrogen oxides (NO x = NO + NO 2 ) are combustion, soils, and lightning. Several epidemiological studies have shown consistent associations of long-term NO 2 exposure with decreased lung function and increased risk of respiratory symptoms [Ackermann-Liebrich et al, 1997;Schindler et al, 1998;Panella et al, 2000;Smith et al, 2000;Gauderman et al, 2000Gauderman et al, , 2002. Strong associations exist between NO 2 and nonaccidental mortality in daily time series studies [Steib et al, 2003;Burnett et al, 2004;Samoli et al, 2006].…”
Section: Introductionmentioning
confidence: 93%
“…The risk of asthma onset or chronic effects on asthma from ambient air pollution exposure has been less clearly identified in epidemiologic studies, although few studies are prospective cohort designs (6)(7)(8)(9)(10)(11)(12)(13). A cohort study of nonsmoking adult Seventh Day Adventists in California followed 10 or more years found associations between the development of asthma and outdoor concentrations of total suspended particulates (11), total suspended sulfate (12), and ozone (O 3 ) (13).…”
Section: Importancementioning
confidence: 99%